SINERGI MULTISTAKEHOLDER DALAM PERCEPATAN SERTIFIKASI TANAH WAKAF: STUDI KASUS KUA SOREANG, PAREPARE - Alfiyah Dhiyaul Auliyah; Rusnaena; Sulkarnain; Nur Fadillah Ramadhani (Indonesia Journal of Zakat and Waqf, 2024)
This study aims to analyze the implementation of collaboration between the Office of Religious Affairs (KUA) of Soreang Sub-district in Parepare City and various stakeholders in optimizing the certification of waqf land. The background of this research lies in the fact that many waqf lands remain uncertified due to low legal awareness, complex administrative procedures, and a lack of inter-agency coordination. Utilizing a qualitative field research approach, data were collected through interviews, observations, and documentation involving key actors such as KUA, the National Land Agency (BPN), the Sub-district Government, and the Ministry of Religious Affairs. The findings reveal that multi-party collaboration—led by KUA with technical support from BPN and administrative facilitation from the Sub-district Government and the Ministry—effectively accelerates the certification process. This collaboration not only enhances the legal security of waqf assets but also strengthens social synergy in the sustainable management of religious endowments. These insights are expected to serve as a model for other regions in improving waqf governance through strategic collaborative approaches.